ANALISIS DEIKSIS DALAM TAJUK RENCANA HARIAN KOMPAS DAN RELEVANSINYA DENGAN PEMBELAJARAN MENULIS TEKS EKSPOSISI - Anggun Citra Dini Dwi Puspitasari (Peneliti.net, 2020)
This research aims to describe the types of deixis contained in the editorial of Kompas edition June 2020 and to describe the relevance between deixis in the editorial of Kompas and learning to writing exposition text. The method used in this research is descriptive qualitative. The data source used is forty eight editorials of Kompas edition June 2020. The results of this research is the types of deixis contained in the editorial of Kompas edition June 2020 and its relevance in learning to writing exposition text in class X. The types of deixis contained in the editorial of Kompas edition June 2020 is five types of deixis, person deixis is 213 words, place deixis is 78 words, time deixis is 110 words, discourse deixis is 198 words, and social deixis is one word. This research can be used as teaching material in learning to writing exposition text, especially on basic competencies developing the contents of the exposition text in oral and/ writing.